2017
DOI: 10.1159/000464118
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Glucagon-Like Peptide-1 Analog on Renal Tubular Injury in Mice on High-Fat Diet

Abstract: Aims: The study aimed to investigate the renoprotective effect of glucagon-like peptide-1 (GLP-1) against renal tubular injury in C57BL/6 mice induced by a high-fat diet (HFD). Methods: Twenty C57BL/6 mice were fed HFD for 12 weeks. Ten of these mice were treated with GLP-1 at 200 µg/kg subcutaneously twice daily for 4 weeks (HFDG group), and the other ten mice received vehicle only (HFD group). Ten mice fed standard rodent chow served as controls (Con group). Body weight, kidney weight, food intake, and systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Liraglutide has been shown to ameliorate early renal injury by activation of the renal Forkhead box protein O1 (FoxO1) in a type 2 diabetic kidney rat model . Pre‐clinical animal studies showed a GLP1‐analog to have a protective effect against saturated fatty acid‐induced kidney tubular cell endoplasmic reticulum stress, and apoptosis, both in vivo and in vitro . Additionally, the reduction in renal injury could be attributed to decreased glucose drag and glomerular hyperfiltration in the setting of obesity during dulaglutide treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liraglutide has been shown to ameliorate early renal injury by activation of the renal Forkhead box protein O1 (FoxO1) in a type 2 diabetic kidney rat model . Pre‐clinical animal studies showed a GLP1‐analog to have a protective effect against saturated fatty acid‐induced kidney tubular cell endoplasmic reticulum stress, and apoptosis, both in vivo and in vitro . Additionally, the reduction in renal injury could be attributed to decreased glucose drag and glomerular hyperfiltration in the setting of obesity during dulaglutide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10 Pre-clinical animal studies showed a GLP1-analog to have a protective effect against saturated fatty acid-induced kidney tubular cell endoplasmic reticulum stress, and apoptosis, both in vivo and in vitro. 11 Additionally, the reduction in renal injury could be attributed to decreased glucose drag and glomerular hyperfiltration in the setting of obesity during dulaglutide treatment. Thus, dulaglutide could be regarded as a valuable asset in the management of type 2 diabetes in SOT patients with renal dysfunction and metabolic syndrome.…”
Section: Renal Dysfunction Is One Of the Frequent Complications In Sotmentioning
confidence: 99%
“…IHC has recently been used for determination and identification of expressed proteins such as lysosome-associated protein transmembrane-4 beta (LAPTM4B) associated with the prognosis of several human malignancies (Xiao et al, 2017), glucagon-like peptide-1 (GLP-1) against renal tubular injury (Guo et al, 2017), and CD147 trans-membrane protein that induces expression and activity of matrix metalloproteinases (MMP) (Dana et al, 2016).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…61 Finally, and with regard to apoptosis, it has been suggested that GLP-1R agonists exert renoprotective effects by targeting cAMP and phosphatidylinositol 3-kinase dependent signalling pathway, which is known to inhibit apoptosis. 62 Other studies documented that anti-apoptotic effect of exendine-4 is by decreasing caspase-3 activity in renal tissue of renal ischaemia reperfusion models. 63 To our knowledge, our study is the first to demonstrate the reno- Bearing in mind the current pharmaceutical use of exendin-4 as a glycaemic control agent, our findings proposes exendine-4 as a promising candidate for prophylactic therapy against CIN in humans, particularly diabetic and renal impairment patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to endothelial dysfunction, it has been postulated that phosphorylation of nuclear factor‐kappa B (NF‐kB), a key nucleus transcriptional factor which regulates the expression of a number of genes may play a key role in the reduction in endothelin‐1 expression as well as in the increase in eNOS expression by GLP‐1R agonists in the endothelial cells . Finally, and with regard to apoptosis, it has been suggested that GLP‐1R agonists exert renoprotective effects by targeting cAMP and phosphatidylinositol 3‐kinase dependent signalling pathway, which is known to inhibit apoptosis . Other studies documented that anti‐apoptotic effect of exendine‐4 is by decreasing caspase‐3 activity in renal tissue of renal ischaemia reperfusion models …”
Section: Discussionmentioning
confidence: 99%